Between a boulder and a hard place: an actualistic experiment to infer the impact of cave roof fall on limb bones and its implications for the archaeological record - Hajdu, Alexandru, author; Glantz, Michelle, advisor; Pante, Michael, committee member; Hess, Ann, committee member (Colorado State University. Libraries, 2022)
Over 50 years of research has highlighted the important role hominins and carnivores play as agents of bone fragmentation. The work has largely been focused on differentiating the assemblages created by hominins from those modified by carnivores. Consequently, cave roof fall and other agents have received relatively little attention in this rich literature. Previous studies of cave roof fall have suggested it can modify assemblages in a manner that mimics hammerstone-on-anvil percussion of bones indicating the need for reliable criteria to distinguish between these two processes. Here, we conduct an actualistic experiment designed to simulate the effects of cave roof fall on bone assemblages. Sixteen (n=16) bison tibiae were fractured in four experiments with drop heights of 4.6 and 7.6 meters and rock weights of 6.8 and 13.6 kilograms. To represent a hominin assemblage sixteen (n=16) tibiae were randomly selected from a hammerstone-on-anvil collection created by Robert Kaplan and stored at Colorado State University. Bone surface modifications (BSM) counts that include pits, notches, grooves, and striations were created for both groups. Additionally, notch measurement ratios, Incipient notch counts, fragment counts, general fragment size frequency distributions, epiphyseal fragment measurements, percentages of fragments with BSMs, and presence/absence of stress relief traces (hackle marks and ribs) were collected from both groups. Results suggest that flake count, pit count and the percentage of fragments with pits and/or grooves are the variables which are different between cave roof fall and hammerstone-on-anvil percussion. These variables are significantly different between the two assemblages; however, they are not applicable to the archaeological record. This is because the traces that these variables were built upon are not distinguishable between the two actors. This qualitative approach to address the equifinality between cave roof fall and hammerstone-on-anvil percussion has failed to provide any valuable insights.
Keywords: bone surface modifications; experimental; taphonomy; cave roof fall; actualistic; rock fall